2017
DOI: 10.1017/s0022029917000619
|View full text |Cite
|
Sign up to set email alerts
|

Rumination time as a potential predictor of common diseases in high-productive Holstein dairy cows

Abstract: We examined the hypothesis that rumination time (RT) could serve as a useful predictor of various common diseases of high producing dairy cows and hence improve herd management and animal wellbeing. We measured the changes in rumination time (RT) in the days before the recording of diseases (specifically: mastitis, reproductive system diseases, locomotor system issues, and gastroenteric diseases). We built predictive models to assess the association between RT and these diseases, using the former as the outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
0
12
1
Order By: Relevance
“…During low ruminal pH, gram-negative bacteria are lysed more rapidly, increasing the concentration of LPS in the rumen (Khafipour et al ., 2011). It has been reported that intramammary infections caused by E. coli are more easily identified because they are characterized by a severe inflammatory response, including sudden shock, sepsis, and often death, caused by the releasing of LPS (Moretti et al ., 2017). The ruminal epithelium is continuously exposed to high level of LPS in cows with SARA.…”
Section: Discussionmentioning
confidence: 99%
“…During low ruminal pH, gram-negative bacteria are lysed more rapidly, increasing the concentration of LPS in the rumen (Khafipour et al ., 2011). It has been reported that intramammary infections caused by E. coli are more easily identified because they are characterized by a severe inflammatory response, including sudden shock, sepsis, and often death, caused by the releasing of LPS (Moretti et al ., 2017). The ruminal epithelium is continuously exposed to high level of LPS in cows with SARA.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of heat stress is determined by a temperature-humidity index (THI) (Armstrong, 1994). In general, physiological changes in heat-stressed cows include impaired rumen function (Bernabucci, 2012), decreased rumination time (Moretti et al, 2017) and feed intake (Wheelock et al, 2010) resulting in decreased milk production, reproductive efficiency and immune functioning. The initial heat stress (environment THI > 72) and moderate heat stress (environment THI > 80) induce panting, increased respiratory rate, lower feed intake, lower production performance, reduced fertility and increased early embryonic death (Jian et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In dairy science, machine learning has been used successfully to predict a whole range of different traits, such as mastitis (Kamphuis et al, 2010;Ebrahimie et al, 2018), methane production (Zheng et al, 2016), and milk production (Gianola et al, 2011). However, despite the advantages of machine learning, other recent studies have used traditional linear methods to predict disease risk (Moretti et al, 2017), methane production (Engelke et al, 2018), and milk production (Wallén et al, 2018).…”
Section: Introductionmentioning
confidence: 99%